Alterações nutricionais em casca e polpa de abóbora decorrentesde diferentes métodos de cozimento - Daiuto, Érica Regina [UNESP]; Vieites, Rogério Lopes [UNESP]; Pigoli, Daniela Regina [UNESP]; Carvalho, Lídia Raquel de [UNESP] (My University, 2012)
The aim of this study was to verify the method and cooking time most suitable for the preparation of squash pulp and pell, to minimize nutrient losses. Peel and slices of squash were subjected to pre cooking tests was iniciating with 0.5 min, 1 min, 1,5 min and successively. Pre test was observed in the texture of the food, to obtain the same texture independent of the type of cooking. The squash pulp and pell were subjected to four types of heat treatment (pressure, immersion, microwave and steam), after been pounded with a mix household and stored at -18 ºC . The proteins, lipids, fibers, sugars reducers and total as well as of ascorbic acid content and minerals ( iron, calcium, zinc, magnesium, potassium, phosphorus and calcium ) were evaluated. The analyses were accomplished in the fresh vegetable and after cooking for the different methods in study. The peel squash presented percentages of nutrients equivalent the pulp could be used in the preparation of meals. They happened nutrient losses in the squash peel and pulp submitted to the different cooking methods in relation to the raw vegetable. The method of steaming and microwave had lower nutritional losses in the squash pulp and peel.

O objetivo desse trabalho foi verificar o método de cozimento mais adequado para o preparo da abóbora,visando minimizar as perdas nutricionais. A casca e polpa da abóbora foram submetidas a pré testes decozimento a fim de se determinar o melhor tempo de cozimento, iniciando-se com 0,5 min, 1 min, 1,5 min esucessivamente. A casca e fatias de abóbora foram submetidas a quatro tipos de tratamentos térmicos(pressão, imersão, microondas e vapor), foram trituradas em mix doméstico e armazenadas à -18ºC. Avaliou-seo teor de proteínas, lipídios, fibras, teores de açúcares redutores e totais assim como de ácido ascórbico eminerais (ferro, zinco, magnésio, potássio, fósforo e cálcio). As análises foram realizadas na hortaliça fresca eapós cozimento pelos diferentes métodos em estudo. A casca da abóbora apresentou porcentagens denutrientes equivalentes aos da polpa podendo ser aproveitada no preparo de refeições. Ocorreram perdas denutrientes na polpa e casca de abóbora submetida aos diferentes métodos de cozimento em relação ao vegetalcru. O método de cozimento no vapor e em microondas resultaram nas menores perdas nutricionais na polpa ecasca de abóbora.
Nutritional alterations in peel and pulp of squash due to different cooking methods
Keywords: Curcubita máxima Duchesne; Vitamin C; Processing; Curcubita máxima Duchesne; Vitamina C; Processamento